The accounting treatment of cryptocurrencies: the perspective of current accounting standards - Sori, Zulkarnain Muhamad; Mohamad, Shamsher; Ahmad, Aimi Adibah Yasmin; Osman, Mohammad Noor Hisham (Universiti Putra Malaysia Press, 2024)
Cryptocurrencies are digital currencies void of any support from regulatory body that is currently in vogue as a medium of exchange and an investment security. This paper examines the accounting treatment for cryptocurrency from the perspective of IFRS and AAOIFI accounting standards and propose actions to standard setters on the best way to treat the Crypto transactions in accounting reports. A proper accounting treatment will allow for a fair reporting of crypto related transactions and facilitate users of financial statements to make objective assessment of this new invention. A content analysis was conducted to review all major accounting standards issued by accounting standards setting bodies for possible accounting treatment for cryptocurrencies. To better understand the issue in practice, an analysis of accounting treatment of cryptocurrencies by 2 companies also was conducted. This study found that there is no suitable accounting standard that could objectively be applied for cryptocurrencies. For example, from the perspective of the current accounting standards, cryptocurrencies match the definition of inventory if it is used as a commodity for broker-trader and intangible asset for others respectively. It is suggested that there an urgent need for the International Accounting Standards Board (IASB) to comprehensively develop accounting standard for cryptocurrency, specifically to develop a specific category for this type of assets to allow a standard treatment for cryptocurrency and fill the gap in the IFRS.